2008
DOI: 10.1007/s00192-008-0697-5
|View full text |Cite
|
Sign up to set email alerts
|

The distribution of different surgical types for female stress urinary incontinence among patients’ age, surgeons’ specialties and hospital accreditations in Taiwan: a descriptive 10-year nationwide study

Abstract: This study aims to identify the changing trends of different surgical types for female stress urinary incontinence (SUI) and the distribution amongst various providers' characteristics. A total of 17,532 women who had undergone surgery for SUI during 1996-2005 were identified from the National Health Insurance Research Database for analysis. Retropubic urethropexy (RPU) was the most common surgical type (43%), followed by tension-free mid-urethral sling (MUS; 24%), and traditional pubovaginal sling (15%). MUS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 25 publications
2
13
0
Order By: Relevance
“…Therefore, patients choose a procedure based upon their personal goals for surgery, their general medical condition, and their concern for prolapse recurrence. This and our previous study also observed that patient age is one of the correlative factors which should be taken into account when selecting an appropriate surgical type [12].…”
Section: Discussionsupporting
confidence: 71%
See 4 more Smart Citations
“…Therefore, patients choose a procedure based upon their personal goals for surgery, their general medical condition, and their concern for prolapse recurrence. This and our previous study also observed that patient age is one of the correlative factors which should be taken into account when selecting an appropriate surgical type [12].…”
Section: Discussionsupporting
confidence: 71%
“…Younger women (<50 years old) were more likely to have received uterine suspension in our study. This finding may be attributable to higher expectations of the quality of life among younger women [12]. Preservation of the uterus was recently shown to positively contribute to a patient's self-esteem, body image, confidence, and sexuality [5,8,17].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations